Providing Peace And Stability In The Society - A Factor Of Spiritual Increase - Baymatov Alisher Kahramonovich (Peerian Journals Publishing, 2024)
In the article, the socio-spiritual factors of ensuring peace and stability in Uzbekistan are described in detail in terms of peace and stability. The positive influence of the ideas of peace and stability on people's well-being and their mutual necessity are described. Currently, the reforms implemented to ensure peace and stability are briefly analyzed.
Keywords: peace; stability; social justice; international peace